VALIDITY OF LEVEL EDUCATION AND INCLUSION IN PRODUCTION PROCESS BY CORRELATION ANALYSIS - Guedes, Alvaro Martim [UNESP]; Bassetto, Camila Fernanda [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This article seeks to demonstrate through empirical basis and correlation analysis, the validity of the statement that the inclusion in the labor market is directly correlated with the level of education, ie with the training received by the individual. The data sources were the Brazilian Institute of Geography and Statistics, IBGE, and Sectors of Economic Activity of the Annual Social Information, RAIS. The analysis covered the period 2002 to 2012 in a municipality of Sao Paulo, with a population of approximately 220,000 inhabitants. The study conducted on the merits was to demonstrate empirically based and analytical resources devoted to statistics that in fact there is clear correlation between school education placements in the labor market of individuals and economic development. This observation was obtained based on salary level, gender and economic sectors (primary, secondary and tertiary). Moreover, the correlation was observed between economic development and schooling, which strengthens the widespread assertion of Education strategic role for a country.
Keywords: Education and develompent; Regional Economic Development; Correlation analysis